TNF-α expression in chronic rhinosinusitis with and without nasal polyps - Irfandy, Dolly; Pramita, Arsia Dilla (Oto Rhino Laryngologica Indonesiana, 2024)
Background: Chronic rhinosinusitis is an inflammatory disease of the nasal and paranasal sinusesmucosa, that is caused by multifactorial factors, and has a complex and influential etiology among variousmicroorganisms (bacteria, fungi, and viruses), environmental contamination (pollutants or cigarette smoke)and immune system instability. Tumor necrosis factor alpha (TNF-α) is one of the crucial cytokinesin the inflammatory process that plays a role in chronic rhinosinusitis. Purpose: To compare TNF-αgene expression levels in chronic rhinosinusitis patients with and without nasal polyps. Method: Thisquantitative study included a cross-sectional design comparative analysis of 24 samples obtained from theethmoid bulla of chronic rhinosinusitis patients. The patients were subjected to a Functional EndoscopicSinus Surgery (FESS) approach at the Rhinology Clinic of Dr. M. Djamil Regional Hospital, Padang.Patients were selected based on inclusion and exclusion criteria. The expression of TNF-α was measuredby using the Real-Time Polymerase Chain Reaction (RT-PCR). The data were analysed by SPSS witha p-value <0.05. Result: The average value of TNF-α expression in chronic rhinosinusitis with polypswas 4.89±12.65, while that of TNF-α expression in chronic rhinosinusitis patients without polyps was2.77±4.22. However, there was no statistical difference between the two groups of study (p-value >0.05).Conclusion: This study demonstrated the increased levels of TNF-α in chronic rhinosinusitis patientswith polyps compared to patients without polyps.